Proceedings of the 2017 International Conference on Education Science and Economic Management (ICESEM 2017) 2017
DOI: 10.2991/icesem-17.2017.57
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Knowledge Sharing on Organizational Performance and the Countermeasures

Abstract: Abstract-The most important part of knowledge management is knowledge sharing, which is the prerequisite for the process of knowledge collection, transfer and reconstruction. Knowledge sharing among employees within an organization is an important means for organizations to gain a competitive advantage. This paper analyzes the connotation, the basic way and the factors that affect the knowledge sharing, then puts forward the knowledge sharing strategy within the organization, and then analyzes the positive and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…When the literature is examined, it is seen that information sharing has important effects on long-term relationships and organisational and individual performance, job satisfaction, organisational success, and competitive advantage (Gehrke & Hasan, 2020;Sönmez-Çakır & Adıgüzel, 2020;Ji & Zou, 2017;Harsono, 2016;Tong et al, 2013;Im & Rai, 2008). In addition, in the study conducted by Al-Shawabkeh (2018), which is very similar to this research, it was revealed that knowledge sharing has a mediating role in organisational ambidexterity.…”
Section: Figure:mentioning
confidence: 99%
See 1 more Smart Citation
“…When the literature is examined, it is seen that information sharing has important effects on long-term relationships and organisational and individual performance, job satisfaction, organisational success, and competitive advantage (Gehrke & Hasan, 2020;Sönmez-Çakır & Adıgüzel, 2020;Ji & Zou, 2017;Harsono, 2016;Tong et al, 2013;Im & Rai, 2008). In addition, in the study conducted by Al-Shawabkeh (2018), which is very similar to this research, it was revealed that knowledge sharing has a mediating role in organisational ambidexterity.…”
Section: Figure:mentioning
confidence: 99%
“…Organisational ambidexterity Çakır & Adıgüzel, 2020;Al-Shawabkeh, 2018;Minister et al, 2017;Ji & Zou, 2017;Vrontis et al, 2017;Savolainen, 2017;Tan et al, 2017;Harsono, 2016;Tong et al, 2013;Im & Rai, 2008) on these issues and the purpose of this research are given below:…”
Section: Communication and Information Sharingmentioning
confidence: 99%